Practice patterns in the management of congestive heart failure and post-discharge quality of life: A hospital-based cross-sectional study - Agam Bansal; Rana P Padappayil; Shwetha Gopal; Mohil Garg; Rajnish Joshi (Journal of Family Medicine and Primary Care, 2020)
Objective: The objective of the study is to identify the etiology, risk factors, frequency of major and minor components of the Framingham criteria for heart failure, discharge medications, mortality, and quality of life after discharge from the hospital, for patients who were admitted to the in-patient unit of a tertiary care hospital in central India, with a diagnosis of congestive heart failure (CHF). Methods: This hospital-based cross-sectional study involved retrospective chart review of patients who were admitted to the in-patient unit with a diagnosis of CHF. These patients were then attempted to reach via their telephone numbers listed in the medical records and their current quality of life was assessed using Euro-QoL 5D questionnaire. Results: In the 69 patients who were admitted to the hospital with congestive cardiac failure during the pre-defined period, ischemic heart disease was the most common etiology and smoking was the most common risk factor for the development of CHF. The most common findings based on Framingham criteria were dyspnea on mild exertion, rales and bilateral ankle edema. It was determined that one-fourth of the individuals were non-compliant to the medical treatment and more than half of the patients had a poor health score. Conclusion: Smoking remains to be a major risk factor for patients to develop ischemic heart disease and subsequent CHF. Patients with congestive cardiac failure also had severe deterioration in their quality of life after discharge from the hospital, implying the need for improving efforts toward prevention and better management.